Analysis of Soil Salinity Distribution in the Wonorejo Mangrove Botanical Gardens, Surabaya - Dinda Ramadhani Putri; Purnomo Edi Sasongko; Rossyda Priyadarshini (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Environmental factors, particularly salinity conditions, influence the function of mangrove forests. Salinity plays a crucial role in the growth, resilience, and zonation of mangrove species. Therefore, it is essential to analyze salinity levels. This study aims to assess salinity levels to determine their effect on soil fertility and to evaluate the influence of the distance from salinity sources in the Wonorejo Mangrove area. Soil sampling was conducted at distances ranging from 5 meters to 60 meters from the riverbank, along three designated paths: J1 (first path), J2 (second path), and J3 (third path). Both composite and intact soil samples were collected. Composite and intact soil samples were taken at intervals from 5 to 60 meters from the riverbank, with each path containing two sampling points, resulting in a total of six sample points (T1, T2, T3, T4, T5, T6), each repeated three times. The observed parameters included soil pH, electrical conductivity (EC), soil permeability, soil texture, cation exchange capacity, and organic carbon content. The results of the chemical and physical analyses of the mangrove forest soil samples indicate that salinity levels range from high to very high. This finding is evidenced by the lowest EC value recorded in soil sample T3U3, which was 15.9 dS/m, indicating high salinity.